Social Welfare Data Collection Information System Innovation Process Through PDKTSAM in Malang City - Palumpun, Aris Sugiarto; Said, Abdulah; Lastiti, Niken (Wacana Journal of Social and Humanity Studies, 2025)
This study uses Rogers' diffusion of innovation theory perspective to examine the Malang City Social Welfare Data Collection (PDKTSAM) innovation's routinization process. The Social Welfare Data Collection aims to identify, classify, and map the welfare conditions of the community to ensure that social assistance and other government programs are on target. The study results indicate that PDKTSAM has become part of the organization's routine activities through the establishment of SOPs, integration with other systems, and ongoing data evaluation and updating mechanisms. Active participation of various stakeholders, policy support, and system modification and adjustment are key factors in ensuring the sustainability of PDKTSAM utilization. However, this study also identified major challenges in the routinization phase, such as data synchronization, updating, and cross-agency coordination. Limited human resources and technological infrastructure are also recognized as obstacles to implementation. Therefore, a holistic and adaptive strategy is needed to overcome these obstacles and ensure the sustainability of PDKTSAM innovation in the long term. With accurate and up-to-date data, the government can design effective policies, reduce poverty, and improve the quality of life of the community as a whole. This data collection also forms the basis for more objective and transparent decision-making in efforts to develop social welfare. Keywords: data evaluation, diffusion of innovation, PDKTSAM, routinization, sustainability